Efektivitas Terapi Swedish Massage sebagai Upaya Penurunan Tekanan Darah pada Pasien Hipertensi: Kajian Literatur - Anindya Petra Bagas Raditya; Stefani Vista Ayu Anggraini; Vinda Dolorosana Kusumawati; Juhdeliena Juhdeliena (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Hypertension is one of the causes of the highest morbidity in the world. In Indonesia, the prevalence rate of hypertension in 2018 reached 34.1% for the population over 18 years of age. There are various efforts that can be made to lower the blood pressure in hypertensive patients, one of which is Swedish massage therapy. Swedish massage therapy is an act of doing massage through effleurage, petrissage, friction, tapotement, and vibration techniques on certain parts of the body for a relaxing effect to lower blood pressure through the release of the hormones adrenaline in the parasympathetic system. This study aimed to determine the effectiveness of Swedish massage therapy as an effort to reduce blood pressure in hypertensive patients. This study uses a literature review design. The data used were taken from two databases, Google Scholar and Research Gate, using boolean AND, and were searched based on specified inclusion and exclusion criteria. Article search results is presented in the PRISMA diagram. The articles obtained are then performed Critical Appraisal and due diligence using Joanna Briggs Institute (JBI) tools, then analysed using the simplified thematic approach. The search results obtained as many as 555 articles on Google Scholar and 36 articles on Research Gate, bringing a total of 591 articles and a total of six articles were researched. In conclusion, Swedish massage therapy is effective in lowering blood pressure in hipertensive patients